Implementation of The Clean and Healthy Living Behavior (PHBS) Fostering Program in Indramayu Regency : Case Study in The Work Area of UPTD Puskesmas Jatibarang - Ismanudin, Ismanudin; Nirwana, Senja (Universitas Wiralodra, 2024)
This study was conducted to determine the implementation of the household PHBS development program in the working area of UPTD Puskesmas Jatibarang. The research focused on motivating, facilitating, directing, communicating, and controlling aspects carried out by UPTD Puskesmas leaders and PHBS program managers in the UPTD Puskesmas Jatibarang working area, Indramayu Regency. In addition, identifying and analyzing the constraining factors in the implementation of the PHBS coaching program. This study used a qualitative method with a descriptive phenomenological approach. Samples were selected purposively, with key informants being the head of the UPTD Puskesmas Jatibarang and the PHBS program manager. Research informants were PHBS cadres, housewives, and community leaders. Data collection techniques through in-depth interviews and observations of PHBS management informants at the puskesmas level, PHBS cadres, housewives, and community leaders, as well as documentation techniques. Data analysis techniques through qualitative data analysis techniques, through data reduction, data display, and conclusion drawing/verification. The results showed that the achievement of 10 indicators of PHBS in the work area of the UPTD Puskesmas Jastibarang in 2011 had reached 82.1%, while in 2012 the program achievement was seen to increase to 90.3% or an average of 86.2% per year. However, judging from the achievement of the total percentage of healthy households in 2012 only reached 36.4% or decreased compared to 2011 which had reached 56.3% of healthy households, so that the PHBS program in the family setting has not been fully effective. There are still internal and external constraints in the management of the PHBS program, as well as the need for coordination and synergistic cooperation with cross-program, cross-sector and other related.